Sunlight & breadcrumbs : making food with creativity & curiosity - Erickson, Renee; Dickerman, Sara, 1971- (Abrams, 2024)
"James Beard Award-winning chef Renee Erickson shares simple details that can elevate everyday meals, in a vibrantly original cookbook that celebrates creativity and is filled with Erickson's photography, paintings, and favorite recipes to make at home."--Back cover.